2012
DOI: 10.1371/journal.pone.0047163
|View full text |Cite
|
Sign up to set email alerts
|

The Transcriptome Profile of the Mosquito Culex quinquefasciatus following Permethrin Selection

Abstract: To gain valuable insights into the gene interaction and the complex regulation system involved in the development of insecticide resistance in mosquitoes Culex quinquefasciatus, we conducted a whole transcriptome analysis of Culex mosquitoes following permethrin selection. Gene expression profiles for the lower resistant parental mosquito strain HAmCqG0 and their permethrin-selected high resistant offspring HAmCqG8 were compared and a total of 367 and 3982 genes were found to be up- and down-regulated, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
67
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 70 publications
2
67
0
1
Order By: Relevance
“…Overexpression of P450 genes has been linked to the development of resistance in many insect species, including Musca domestica 5-10, Culex quinquefasciatus 11-13, Culex pipiens quinquefasciatus 14, Drosophila 15, 16, Aedes aegypti 17, Anopheles gambiae 18, Helicoverpa armigera 19, Tribolium castaneum 20, Bemisia tabaci 21, 22 , and Trialeurodes vaporariorum 23. In a recent study, Reid et al 24 used RNAseq methodology to conduct a whole transcriptome analysis of Culex quinquefasciatus in permethrin resistant mosquitoes and found that the overrepresented functional categories were mainly among the P450 genes, which may indicate that the overexpression of multiple P450 genes is a key factor governing the increased levels of detoxification of insecticides and insecticide resistance in Culex mosquitoes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of P450 genes has been linked to the development of resistance in many insect species, including Musca domestica 5-10, Culex quinquefasciatus 11-13, Culex pipiens quinquefasciatus 14, Drosophila 15, 16, Aedes aegypti 17, Anopheles gambiae 18, Helicoverpa armigera 19, Tribolium castaneum 20, Bemisia tabaci 21, 22 , and Trialeurodes vaporariorum 23. In a recent study, Reid et al 24 used RNAseq methodology to conduct a whole transcriptome analysis of Culex quinquefasciatus in permethrin resistant mosquitoes and found that the overrepresented functional categories were mainly among the P450 genes, which may indicate that the overexpression of multiple P450 genes is a key factor governing the increased levels of detoxification of insecticides and insecticide resistance in Culex mosquitoes.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the development of resistance to insecticides, especially to pyrethroids, in mosquito vectors has become a global problem 46-51. Our previous studies on whole transcriptome analyses of insecticide resistance 24 and genome analyses of cytochrome P450s and their expression profiles 12 in insecticide resistant mosquitoes have identified multiple up-regulated P450 genes in Cx. quinquefasciatus that may be responsible for the development of resistance to insecticides such as permethrin.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, insecticides induce physiological changes in mosquitoes such as a thickening of the epidermis, which subsequently lowers their permeability to insecticides (Wood et al 2010). Studies investigating the mechanisms of pyrethroid resistance have identified other resistance-related genes, such as UDP-glycosyltransferases , Bozzolan et al 2014) and serine proteases (Reid et al 2012, Strachecka et al 2013.…”
mentioning
confidence: 99%
“…Together with chitin, the cuticle serves as a barrier to the external environment (Papandreou et al 2010). In recent years, the rapid development of advanced biological technologies and transcriptomic and proteomic analyses of sensitive and resistant insects have revealed differential expression of ICPs, such as CPR, CPLC, and CPLCG subfamily members (Awolola et al 2009; Nkya et al 2014; Reid et al 2012; Silva et al 2012). In Anopheles gambiae , temporal and spatial differences in transcript abundance and protein localization mean that the structural cuticular proteins account for only about 2% of its protein coding genes.…”
Section: Discussionmentioning
confidence: 99%